Identification of the Overall Slope Pit Angle Value for Erosion Control in Disposal Land - Doli Jumat Rianto; Aji Marwadi; Shenny Linggasari (Lembaga Penelititan dan Pengabdian kepada Masyarakat - Institut Teknologi Adhi Tama Suraba, 2023)
Open-pit mining can cause changes in environmental conditions, especially in disposal land. The formation of gully erosion on disposal land tends to increase as the area of open land increases. The aim of this research is to calculate the amount of erosion and the geometry of the bench terrace as a form of recommendation for reducing the rate of erosion. The methodology used is the USLE (Universal Soil Loss Equation) method approach in predicting the amount of erosion and an empirical approach in providing recommendations to reduce the rate of erosion for conservation measures in the form of bench terraces. The results showed that the erosion formed on disposal land was 123.43 tons/ha/year with a range of 60-180 tons/ha/year in the category of moderate erosion hazard. While for the dimensions of bench terraces recommended on disposal land, the overall slope pit angle value was 46,60 with a maximum single slope pit angle on the bench of 600 (16.6%). Bench dimensions in the form of bench terraces will have a major influence on the overall slope pit angle value formed. The smaller the width of the bench formed with the single slope pit angle, the greater the value of the overall slope pit angle formed. In addition to the width of the bench that affects the value of the overall slope pit angle is the height of the disposal slope. The height of the disposal slope will be directly proportional to the decrease in the overall pit angle slope, to the number of benches formed. With soil conservation measures in the form of traditional terraces in the form of bench terraces with a value factor of 0.4 in open land without vegetation, it can decrease from 123.43% (tons/ha/year) to 49.37 tons/ha/year ranging from 15-60 tons/ha/year with the category of low erosion hazard level, and or about 39% reduction in erosion that occurs.